2015
DOI: 10.1111/jep.12399
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and drug compliance: their interrelationship in rheumatic patients

Abstract: Doctors caring for rheumatic patients should focus their efforts on strengthening drug compliance in patients with higher QoL where it seems that lower compliance is more likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
1
16
0
1
Order By: Relevance
“…This study demonstrated that using GC has better adherence because most patients with adherence to medication were diagnosed with SLE and RA; in other words, GC was their key drug to relieve symptoms. 28 Different from previous studies, 29 , 30 higher education may contribute to poorer adherence. Maybe the patients with higher education in the cohort were more worried about rheumatic medication-related questions, such as side effects.…”
Section: Discussionmentioning
confidence: 67%
“…This study demonstrated that using GC has better adherence because most patients with adherence to medication were diagnosed with SLE and RA; in other words, GC was their key drug to relieve symptoms. 28 Different from previous studies, 29 , 30 higher education may contribute to poorer adherence. Maybe the patients with higher education in the cohort were more worried about rheumatic medication-related questions, such as side effects.…”
Section: Discussionmentioning
confidence: 67%
“… 36 , 37 Another study recruited patients through the British Society for Rheumatology Biologics Register for RA – a UK-wide prospective observational cohort study established in 2001 for the purpose of monitoring the long-term safety of biologic therapy. 38 In regard to study design, four had a cross-sectional design, 27 , 28 , 31 , 32 five were retrospective cohort studies, 24 26 , 34 , 35 and six were prospective studies. 29 , 30 , 33 , 36 38 …”
Section: Resultsmentioning
confidence: 99%
“…Hromadkova et al 26 assessed the relationship between drug compliance and HRQoL in patients with different rheumatic disorders, including SpA. A significantly negative correlation between compliance and HRQoL PCS was found in SpA patients, suggesting that patients with worse HRQoL might be more compliant with treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For long-term persistence, Favalli et al 43 reported cumulative 8-year retention of 57.2% for axSpA and 51.9% for PsA. Finally, related to compliance, Hromadkove et al 26 reported that only 38.3% of patients with AS were compliant with BA treatment, as indicated by Compliance Questionnaire Rheumatology score 80).…”
Section: Resultsmentioning
confidence: 99%